Simulation of Ground Settlement Using Plaxis for the Pekanbaru-Padang Toll Road Construction Project: A Detailed Analysis - Saragih, Muhammad Sultan Mubaraq; Wulandari, Tika Ermita (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
Geotechnical issues often include settlement and soil bearing capacity, which serve as the foundation for toll roads. Each toll road is designed with specific loads and elevations, which sometimes cannot be supported by the consolidation of the existing soil due to the soft soil characteristics. Soil improvement methods such as replacement (soil material replacement) and preloading are commonly used to enchace the shear strength of soft soils. This analysis aims to evaluate and compare the amount of consolidation settlement analytically using modeling in Plaxis 2D with a very fine mesh type, using settlement plate data from the field. The analysis compares the amount of consolidation settlement through Plaxis 2D modeling with a very fine mesh type and field settlement plate data. From the analysis the consolidation time using Plaxis 2D modeling is found to be 149 days, while the settlement time from the settlement plate data is 39 days. The consolidation settlement obtained from the plaxis 2D model with a very fine mesh is 0.056 meters, whereas the settlement from the settlement plate data is 0.416 meters, with a percentage difference of 86.53%. It can be concluded that the significant difference between the field data and the Plaxis 2D analysis results is due to the lack of data available for each soil layer.